Influence of dabigatran and rivaroxaban on routine coagulation assays - Blerk, Marjan Van; Bailleul, Els; Chatelain, Bernard; Demulder, Anne; Devreese, Katrien; Douxfils, Jonathan; Jochmans, Kristin; Mullier, François; Wijns, Walter; Soumali, Mohamed Rida; Coucke, Wim; Vernelen, Kris; Walle, Philippe Van de (Thrombosis and Haemostasis, 2015)
The Belgian national External Quality Assessment Scheme performed a nationwide survey using lyophilised plasma samples spiked with dabigatran or rivaroxaban to demonstrate to the Belgian clinical laboratories how these drugs affect their routine coagulation assays prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen and antithrombin. Virtually all Belgian laboratories performing routine coagulation testing (189/192) participated in the survey. Both, dabigatran and rivaroxaban significantly prolonged the PT and aPTT in a concentration- and reagent-dependent manner. PT reagents were more influenced by rivaroxaban than by dabigatran and aPTT reagents more influenced by dabigatran than by rivaroxaban. Among PT reagents, Neoplastin R® was the most sensitive to rivaroxaban and Innovin ® and Thromborel S® the least sensitive. Converting PT results to INR only increased the variability between reagents. Among aPTT reagents, Actin FSL® was the least sensitive to dabigatran while the other aPTT reagents showed slightly higher sensitivities. The presence of dabigatran led to falsely reduced fibrinogen concentrations when measured with a low thrombin concentration reagent. The presence of dabigatran caused an overestimation of the antithrombin level when measured with a thrombin-based activity assay and the presence of rivaroxaban an overestimation of the antithrombin level when measured with a FXa-based assay. Instrument-related differences were found for all tested parameters. In conclusion, this paper provides detailed information on the effect of dabigatran and rivaroxaban on routine coagulation assays as performed with a large number of reagent/instrument combinations.
Keywords: Dabigatran; external quality assessment; rivaroxaban; routine coagulation assays